Evaluation of prevailing draft loads in the couplings of the electric trains - V. I. Belyaev; D. V. Gorskiy; D. A. Stupin; A. N. Konyshkov (Вестник Научно-исследовательского института железнодорожного транспорта, 2022)
Introduction. Until now, the requirements for manual and automatic couplers for locomotive-hauled passenger carriages and electric trains have been completely identical, despite the significantly lower level of longitudinal forces during the movement of multi-unit rolling stock with distributed traction. The introduction of specialised designs of coupling devices for electric trains led to the development of strength requirements that enable the creation of new models with smaller dimensions and weight. Operating experience has shown that parts of couplings may be destroyed, leading to the uncoupling of trains. Fatigue damage may cause accidents. However, there were studies of the draft loads of electric trains couplers in operation, on the basis of which it was possible to develop regulatory requirements for specialised coupling devices.Materials and methods. The authors measured the forces acting in the couplings of electric trains of various categories and types during normal operation, as well as the frequencies of the occurrence of forces of various levels. The article includes histograms based on the results of processing the received data showing the distribution of longitudinal forces acting on the inter-car couplers and the parameter characterising the accumulation of fatigue damage per 100,000 km. Results. According to the results of processing of the experimental data, the calculation of the accumulation of fatigue damage to the couplers was carried out and the requirements for their expected service life were established. Test procedures have also been developed to evaluate strength and fatigue resistance under high-cycle and low-cycle loading conditions. The article provides ground for introducing a correction factor into the procedure for processing test results, which makes it possible to perform life tests on equipment with different values of the load cycle asymmetry factor.Discussion and conclusion. The authors have evaluated the draft loads in coupling devices during the operation of electric trains, on the basis of which technical requirements and test methods were developed and approved by JSC Russian Railways. Development and acceptance of all new models of coupling devices for electric trains will be carried out in accordance with these regulatory documents.